Answer:
y = -3x + 6
Step-by-step explanation:
Slope-intercept form:
y = mx + b
m (slope) =
or -3
b (y-intercept, or where the line crosses the y-axis) = 6
y = -3x + 6
Answer:
x = 0 or x = 3
Step-by-step explanation:
if f(x) = g(x) then – x2 + 4x + 1 = x + 1
add the like terms
-x^2 +3x = 0
-x (x-3) = 0 then x is either 0 or 3
Answer:
(2,-3)(6,5)
Step-by-step explanation:
We can use substitution to get the equation: x^2-6x+5 = 2x-7
Solve:
x^2-6x+5 = 2x-7
x^2 = 8x-12
x^2-8x+12 = 0 (we now have a polynomial)
(x-6)(x-2) = 0 (set each equation to equal 0 and solve)
x-6 = 0 --> x=6
x-2 = 0 --> x=2
To get the Y coordinates:
y=2(2)-7 --> y = -3
y = 2(6)-7 --> y = 5
Check work:
5 = 6^2-6(6)+5 --> 5 = 36-36 +5 --> 5=5
-3 = 2^2-6(2)+5 --> -3 = 4-12+5 --> -3=-3
Answer:
the answer is commutative property
Step-by-step explanation:
commutative property is when both constants or variables don't change value when you move them from one side of the equal sign to another such as "a+b = b+a" or " a=b; b=a" both examples do not change value